TEKNOLOGI FITOREMEDIASI UNTUK PENANGANAN PENCEMARAN LOGAM BERAT DI LAHAN PERTANIAN DI KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - MMA. Retno Rosariastuti; Supriyadi Supriyadi; Wiwin Widiastuti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
Research aim of heavy metal pollution handling in agricultural land use fitoremediation technologyis to know the effectivity of hemp and mendong plant used and it’s combination with rhizobacterial isolates Agrobacterium sp I3 or organic materials in order to decrease the levels of heavy metal contamination in the soil such as cromium (Cr), cadmium (Cd) and plumbum (Pb).The research was conducted in Waru Village Kebakkramat Sub-District Karanganyar Regency in 2016. The location is a subdistrict in Karanganuyar Regency whose area has many industries, mainly textile industry.Industrial wastewater in this region is widely used to irrigate rice fields by farmers, so the paddy fields have been polluted by Cr, Cd and Pb.Therefore, it is necessary to decrease the contamination of heavy metals in paddy fields with the selection of environmentally friendly remediation technology, low cost, easy and sustainable.The method of remediation in that category is bioremediation using a plant called phytoremediation.For that required plants that have rapid growth and high metal absorption capability.The character are owned by hemp and mendong plants.Based on previous research obtained Agrobacterium sp I3 rhizobacteria which proved able to increase the uptake of Cromium by hemp plant.The research result showed that hemp and mendong plants can absorb metal either Pb, Cd, or Cr.Based on the amount of metal absorption value in root and plant canopy, hemp plant and mendong shows its ability as hyper akumulator plant (the amount of uptake ≥ 100 ppm).The highest decrease of soil Pb content was 39,406% without treatment of basic fertilizer, with rhizobacterial inoculation Agrobacterium sp I3 and hemp plant.The highest decrease of soil Cd content was 56,604% with treatment with basic fertilizer, with inoculation of rhizobacteria Agrobacterium sp I3 and mendong plant.The highest decrease of Cr content of soil was 42,27% with treatment of basic fertilizer, without inoculation of Agrobacterium sp sp I3 and without hemp and mendong plants.